PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Warna Alam Indonesia) - Wirawan, Fajar; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2015)
The research aims to examine and analyzethe influence of leadership style and Motivation toward performance of employee in PT Warna Alam Indonesia. Data collected through distribution of question naires and it is implemented to PT Warna Alam Indonesia 60 employee.Analysis Of data in this research using the help of SPSS version 16.Analysis technique use dismultiple regression by the least squares equations and hypothesist estingusing the-statistic for testing the partial Regression coefficients with the level of significance of 5%. It also tested validity test, regression analysis, and the classical assumptions that included normality test, multicollinearity test and heteroscedasticity test.Based on the results of the study found no variables that deviate from the classical assumptions, this suggests that the available data has been qualified to Use the model of multiple linear regression equation. From the results showed that the variable leadership style and motivation is partially positive significantly. The predictive capability of the two variables on performance employee of 39,7%.